The Applications of Nanotechnology in Crop Production - Liu, Chenxu; Zhou, Hui; Zhou, Jie (Molecules (Basel, Switzerland), 2021)
With the frequent occurrence of extreme climate, global agriculture is confronted with unprecedented challenges, including increased food demand and a decline in crop production. Nanotechnology is a promising way to boost crop production, enhance crop tolerance and decrease the environmental pollution. In this review, we summarize the recent findings regarding innovative nanotechnology in crop production, which could help us respond to agricultural challenges. Nanotechnology, which involves the use of nanomaterials as carriers, has a number of diverse applications in plant growth and crop production, including in nanofertilizers, nanopesticides, nanosensors and nanobiotechnology. The unique structures of nanomaterials such as high specific surface area, centralized distribution size and excellent biocompatibility facilitate the efficacy and stability of agro-chemicals. Besides, using appropriate nanomaterials in plant growth stages or stress conditions effectively promote plant growth and increase tolerance to stresses. Moreover, emerging nanotools and nanobiotechnology provide a new platform to monitor and modify crops at the molecular level.